Accounting graduates: are they still accountants? / Erlane K Ghani … [et al.] - K Ghani, Erlane; Muhammad, Kamaruzzaman; Mat Tarmezi, Nur Azrin; Mohd Ali, Mazurina; Abdullah, Nabilah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alame, 2019)
This study examines the accounting graduates of a public university in Malaysia. Specifically, this study examines whether the accounting graduates of a public university in Malaysia are in the accounting profession or whether they are in a profession that is not related to accounting. This study also determines whether the accounting graduates’ demographic profile influence their profession. This study utilises online questionnaire on 1003 accounting graduates in the largest public university in Malaysia. The accounting graduates graduated from the period between 2007 and 2017. The results show that most of the accounting graduates are working as accountants or accounting related positions in various industries. Surprisingly, this study shows an alarming sign of accounting graduates not in the accounting profession. This study also shows that the accounting graduates’ demographic profile in terms of gender, age and work sector influence their choice of profession. This study contributes to the existing literature by providing some awareness on the factors influencing the accounting graduates’ choice of profession. The findings in this study could assist the universities to identify strategies in hindering the accounting graduates from leaving to another profession.